Solid-State NMR Spectroscopy of Protein Complexes - Sun, Shangjin (Methods Mol Biol, 2012)
Protein-protein interactions are vital for many biological processes. These interactions often result in the formation of protein assemblies that are large in size, insoluble and difficult to crystallize, and therefore are challenging to study by structure biology techniques, such as single crystal X-ray diffraction and solution NMR spectroscopy. Solid-state NMR (SSNMR) spectroscopy is emerging as a promising technique for studies of such protein assemblies because it is not limited by molecular size, solubility or lack of long-range order. In the past several years, we have applied magic angle spinning SSNMR based methods to study several protein complexes. In this chapter, we discuss the general solid-state NMR methodologies employed for structural and dynamics analyses of protein complexes with specific examples from our work on thioredoxin reassemblies, HIV-1 capsid protein assemblies and microtubule-associated protein assemblies. We present protocols for sample preparation and characterization, pulse sequences, SSNMR spectra collection and data analysis.